2012
DOI: 10.1016/j.urology.2012.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Role of M2 and M3 Muscarinic Acetylcholine Receptor Subtypes in Activation of Bladder Afferent Pathways in Spinal Cord Injured Rats

Abstract: Purpose In this study, we evaluated the role of M2 and M3 mAChR subtypes in activation of bladder afferent pathways in rats with chronic spinal cord injury (SCI). Materials and Methods Adult female Sprague-Dawley rats were spinalized at the Th9 level. Continuous cystometry was performed under an awake condition 2 or 4 weeks after SCI. The effects of intravesical administration of an mAChR agonist (oxotremorine-M; Oxo-M), a non-selective antagonist (atropine), an M2-selective antagonist (methoctramine) and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…This was instituted after previous NHANES installments demonstrated significant deficiencies within the U.S. population and it was discovered that folic acid supplementation could help prevent neural tube defects. (2, 4) Since that time, there have been multiple studies that have shown significant increases in overall serum folate concentrations. (2, 5, 15) To our knowledge, this is the first study that specifically examines the relationship between serum folate and varying levels of DFE intake over the spectrum of ages in United States males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was instituted after previous NHANES installments demonstrated significant deficiencies within the U.S. population and it was discovered that folic acid supplementation could help prevent neural tube defects. (2, 4) Since that time, there have been multiple studies that have shown significant increases in overall serum folate concentrations. (2, 5, 15) To our knowledge, this is the first study that specifically examines the relationship between serum folate and varying levels of DFE intake over the spectrum of ages in United States males.…”
Section: Discussionmentioning
confidence: 99%
“…The second and third installments of NHANES, between 1976–1980 and 1988–1994 respectively, demonstrated significant folate deficiencies (serum folate < 6.81nM) in some populations. (2, 3) Due to the findings that folic acid supplementation could help reduce fetal neural tube defects,(4) fortification of U.S. cereal-grain products became mandatory in 1998. Population based analysis since that time has shown, on average, an approximately 2.5 fold increase in serum folate concentrations compared to pre-fortification.…”
Section: Introductionmentioning
confidence: 99%
“…All drugs were obtained from Sigma–Aldrich Co. The drugs were infused intravesically in concentrations that were determined in pilot experiments or were selected based on concentrations shown in previous studies in rats to be effective in altering reflex bladder activity (Kullmann et al, 2008b; Masuda et al, 2006; Matsumoto et al, 2010, 2012) or bladder afferent nerve activity (Yu and de Groat, 2010; Yu et al, 2016) after intravesical administration.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of cholinergic receptors near the lumenal surface of the bladder by intravesical administration of muscarinic (Kullmann et al, 2008b; Matsumoto et al, 2010) or nicotinic cholinergic receptor agonists (Beckel et al, 2006; Beckel and Birder, 2012; Masuda et al, 2006) modulates reflex bladder activity in spinal cord intact and in chronic spinal cord transected rats (Matsumoto et al, 2012). These effects are attributed to changes in bladder afferent firing.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that the non‐voiding contraction (NVC) in SCI rats are mediated predominantly by C‐fiber afferents while A δ‐fiber afferents are involved in voiding reflexes in spinal intact rats. In addition, studies reported that the M 3 receptor may play an important role in the NDO after SCI, though there was no significant difference in M 3 receptor protein expression between SCI rats and normal control . For example, activation of muscarinic receptor could enhance NDO through increasing C‐fiber afferents mediated activity in SCI rats and muscarinic receptor antagonists were implicated in the desensitization of C‐fiber afferents, whereas it is hard to reach the detrusor layer and modulate detrusor muscle activity by intravesical administration .…”
Section: Introductionmentioning
confidence: 99%